(untitled) (Herald of the National Children’s Medical Center, 2025)
Aim. Dermo-respiratory syndrome (DRS) in children is a multifactorial condition frequently associ- ated with allergic manifestations and recurrent respiratory diseases. Vitamin D deficiency has been proposed as a contributing factor to immune dysregulation in this patient population, yet its role remains insufficiently defined in the pediatric setting. Materials and methods. This prospective study included 151 children aged 3–15 years diagnosed with DRS and 50 age-matched healthy controls. Anthropometric measurements, body mass index (BMI), serum 25(OH)D levels, and relevant biochemical and hematological markers were evaluated. Subgroups were analyzed based on vitamin D status, severity of clinical manifestations, and frequency of exacerbations. Statistical analysis included ANOVA and X² tests to assess differences between groups. Results. Vitamin D deficiency (<20 ng/mL) was detected in 72.2% of children with DRS, compared to 18% in controls (p<0.001). Children with severe deficiency demonstrated higher BMI values (p<0.05), increased frequency of respiratory exacerbations (mean 5.1 ± 1.3 per year), and more pronounced dermatological symptoms. Correlation analysis revealed a significant inverse relationship between serum 25(OH)D levels and both exacerbation frequency (r = –0.56) and BMI (r = –0.43). Implementation of vitamin D supplementation over a 6-month follow-up resulted in improved clinical scores and reduced exacerbation frequency by 38%. Conclusion. Vitamin D deficiency is highly prevalent among children with dermo-respiratory syn- drome and correlates with disease severity and comorbid obesity. Routine screening and correction of vitamin D status should be considered as part of the comprehensive management strategy for pediatric DRS.